Perancangan Interior Pusat Pendidikan Anak Jalanan di Surabaya - Mariana Wibowo, Nike Adriyanti (Intra, 2014)
Children in the street is one of the social problems that exist in Indonesia, especially in Surabaya, one of the major cities with high population . Poverty is the main cause that forces children to seek income and living on the streets to help the familyâs economy . Street environment is possible to bring negative impacts on children who lives in the street. The education center of children in the street with Green Design concept aims to facilitate street children in order to get an education and a decent life like the kids in general through interior design with green design concept applied in order to build and develop the nation . Design methods that will be used is an analytical method to conduct field surveys and direct interviews to find out the problems, then collect data, and analyze the data as a basis for designing the interior with standard literature. Interior design of street childrenâs education center with Green Design concept is not only the result of social problem solving that occurs but also as a life-support and the learning process for the better.